Determining complex petroleum migration pathways along faults and sandbodies: a new method and application - Jijian, Shi; Guang, Fu; Lili, Li (Frontiers in Earth Science, 2024)
Introduction: The reservoir-forming rule in the paleo-slope zone outside petroliferous basins’ source kitchens of the eastern basin in China is unclear, manifested in the distribution of oil and gas in complex multi-layers. This study focuses on petroleum migration along faults and sandbodies to clarify this question and improve the exploration efficiency of petroleum in areas with similar geological conditions. Method: We summarized two models of petroleum migration based on two factors: the connected sandbodies and the vertical unsealing faults. Model I is conducive to the migration of hydrocarbons within a single layer, while Model II is conducive to the vertical migration of hydrocarbons across layers. Combining the means for evaluating fault sealing and sandbody connectivity, integrating these models could form a set of characterization methods for the distribution of the complex fluid migration pathways. Results: This method is applied to characterize the complex multilayer migration pathways distribution in the first and second members of the Shahejie Formation in the central-southern area of the Wen’an Slope in the Baxian Sag, Jizhong Depression, Bohai Bay Basin, China. The results show that, in the first and second members of the Shahejie Formation in the central-southern area of the Wen’an Slope, the area for Model II is mainly distributed in the central-eastern regions. The second member has a Model I area distributed in its western region, and the first member has a Model I area distributed in its centraleastern parts. The latter distribution area is larger than the former. According to hydrocarbon migration analysis, the first member is more conducive to large regional migration and accumulation of hydrocarbons than the second member. Discussion: The predicted result of petroleum migration is consistent with the hydrocarbon distribution found in the central-southern areas of the Wen’an Slope, which is that oil and gas distribution in the first member is significantly greater than that in the second member. Thus, our method is feasible for characterizing the regional distribution of complex multi-layer migration pathways in simple tectonic setting and oil source conditions. However, further research is still needed to increase the effectiveness of present petroleum migration analysis.